Australia's Immigration Selection System and Labour Market Outcomes in a Family Context: Evidence from Administrative Data - Cahit Guven; Lan Anh Tong; Mutlu Yuksel (Institute of Labor Economics (IZA), 2020)
This paper examines the efficacy of Australian points system in a family context among working-age permanent resident immigrants who arrived between 2000 and 2011 when there was a major focus on skills selection. 67% of these immigrants were granted a skilled visa while 25% hold a spousal visa (spouses of Australian citizens). More than half of the skilled visa recipients are the spouses of the primary applicants. Primary applicants among skilled visa holders are assessed for their skills in line with Australian points system but secondary applicants, such as spouses, among skilled visa holders and spousal visa holders are not subject to any skills assessment before becoming permanent residents. We study differences in economic outcomes by permanent visa types and the role of points system factors in explaining these differences using Personal Income Tax and Migrants Integrated Dataset and Australian Census Longitudinal Dataset. We find that primary skilled visa holders earn at least 26-28 percent higher than spousal visa holders and this is similar for both genders. However, spouses of primary skilled visa holders earn 13-18 percent higher than spousal visa holders. This difference is higher among females than males. Occupation differences can account for nearly half of the differences in income and can entirely capture the role of education and English proficiency. Primary skilled immigrants and their spouses have higher rates of labour force participation and employment than spousal visa holders starting in the first year of arrival and the gap is much higher for primary skilled visa holders but these differences do not disappear quickly.
Keywords: J12; J13; J24; J31; J61; J62; 330; points system; immigration; administrative data; Australia